EFFECT OF SINGLE INJECTION OF VITAMIN D (CHOLECALCIFEROL, 6 LAC IU) IN ADULTS: DOES BODY MASS INDEX DETERMINE DOSAGE FREQUENCY AND RISE IN SERUM 25(OH)D3 LEVEL? - Purohit, Vinay (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: Vitamin D deficiency (VDD) is a widespread problem in all age groups and socioeconomic strata. Cholecalciferol intramuscular (IM) injections are often prescribed to treat VDD. Response to cholecalciferol injection is not uniform in all subjects. Methods: We enrolled 65 ostensibly healthy adult volunteers in a vitamin D awareness camp. They were screened for VDD by measuring their serum 25(OH)D3 level. Of 65 subjects, 58 were found to be deficient, 2 insufficient and 5 sufficient. Their body mass indices (BMI) were calculated by measuring height and weight. A total of 31 subjects preferred taking single IM injection of cholecalciferol (6 lac IU) to correct their deficiency and decided to comply with follow-up 25(OH)D3 measurement at day 15, 60 (2 months) and 180 (6 months). Results: Mean values for 25(OH)D3 in 31 subjects were 12.88Â±2.55 ng/ml, 29.33Â±14.40 ng/ml, 47.27Â±11.09 ng/ml, and 24.59Â±8.19 ng/ml at baseline, day 15, 60, and 180. Mean 25(OH)D3 levels at baseline, day 15, 60, and 180 were 12.80Â±2.40 ng/ml, 24.85Â±10.60 ng/ml, 44.76Â±8.85 ng/ml, and 25.05Â±9.62 in obeseâ€ subjects, 13.50Â±3.06 ng/ml, 28.25Â±11.45 ng/ml, 44.70Â±10.40 ng/ml, and 24.48Â±6.81 in overweightâ€ individuals and 12.43Â±2.72 ng/ml, 44.06Â±19.26 ng/ml, 61.16Â±6.96 ng/ml, and 23.33Â±5.42 in normalâ€ subjects. Values between groups were found to be significantly different at day 15 and 60 after applying one-way ANOVA. Conclusion: All subjects, after taking single cholecalciferol IM injection (6 lac IU), had their 25(OH)D3 levels raised to normal within 2 months but reached insufficient range in 6 months. Though the rise in 25(OH)D3 was significantly faster in those having normal BMI than in the subjects having higher BMI. One injection of 6 lac IU cholecalciferol, every 6 months seems to be an effective and safe way of treating VDD. Keywords: Vitamin D, Cholecalciferol injection, Body Mass Index, BMI, 25(OH)D3